Does universities foster creativity and innovation: a study of Universiti Teknologi MARA, Malaysia / Azlin Shafinaz Arshad ... [et al.] - Arshad, Azlin Shafinaz; Kamall Khan, Yasmin; Arshad, Afiza Azura; Abdul Halil, Nurul Hafez (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
Creativity and innovation have been the heart of many universities around the world and many activities are being organized in nurturing creativity and innovation especially to students. The aim of this study is to explore students' perception towards the role of university in fostering creativity and innovation. Data was collected using survey questionnaire which was distributed at an innovation competition organized by Malaysian Academy of Entrepreneurship Development (MASMED), Universiti Teknologi MARA (UiTM) using convenience sampling. The respondents were undergraduate students from 13 campuses of UiTM. A total of 104 survey questionnaire were distributed but only 81 was collected and deemed to be useful. The study found that the students perceived personal attitude, curriculum as well as university support play a part in fostering creativity and innovation. This is evident where the majority of the items were rated high by the students with the mean values were above 4. Moreover, the students also believed that the curriculum offered in the university has the highest influence towards creativity and innovation compared to the university support and personal attitude. The results of the study provided some insights on how students perceived creativity and innovation.